2005
DOI: 10.1002/prot.20547
|View full text |Cite
|
Sign up to set email alerts
|

Hypocrea jecorina (Trichoderma reesei) Cel7A as a molecular machine: A docking study

Abstract: Hypocrea jecorina (formerly Trichoderma reesei) Cel7A has a catalytic domain (CD) and a cellulose-binding domain (CBD) separated by a highly glycosylated linker. Very little is known of how the 2 domains interact to degrade crystalline cellulose. Based on the interaction energies and forces on cello-oligosaccharides computationally docked to the CD and CBD, we propose a molecular machine model, where the CBD wedges itself under a free chain end on the crystalline cellulose surface and feeds it to the CD active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 41 publications
4
60
1
Order By: Relevance
“…7A) found from the values of rate constants k (Table 1) were in the range of 30 s, and during this time, an average of 66 Ϯ 7 cellobiose units were released (Table 1). Although different scenarios for CBM-assisted catalysis have been proposed (15,16), the supporting biochemical evidence has remained elusive (17). Here we measured somewhat lower P app and k cat values for CD TrCel7A compared with the intact enzyme, but the differences may not be significant, considering the error limits (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7A) found from the values of rate constants k (Table 1) were in the range of 30 s, and during this time, an average of 66 Ϯ 7 cellobiose units were released (Table 1). Although different scenarios for CBM-assisted catalysis have been proposed (15,16), the supporting biochemical evidence has remained elusive (17). Here we measured somewhat lower P app and k cat values for CD TrCel7A compared with the intact enzyme, but the differences may not be significant, considering the error limits (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…CBMs have also targeting function (11)(12)(13)(14), and it has been demonstrated that TrCel7A is targeted to the hydrophobic phases of cellulose crystal (14). Although molecular dynamics simulations have predicted more intimate roles for CBM in catalysis like disengagement of cellulose chains from the crystal lattice (15) or aiding processive movement (16), the biochemical evidence of such roles is elusive (17). Besides TrCel7A, T. reesei also secretes a less abundant CBH, TrCel6A, and a number of EGs that include TrCel7B, TrCel5A, and TrCel12A.…”
mentioning
confidence: 99%
“…In particular, breaking a ring down into groups of flaps that move as the ring puckers allows a quantitative assessment of the effect that intermolecular forces on pendant atoms [10][11][12] will have upon the conformation of the ring to which they are attached. Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 This has been used to elucidate the transitionstate pathway of a pyranose conformation. 12 However, this method is very subjective.…”
Section: Implications Of Puckering Coordinatesmentioning
confidence: 99%
“…The evidence suggests that such surface modifications on cellulose are likely caused by the decrystallization activity of cellulase. The mechanistic model for enzymatic decrystallization proposed by Reilly and coworkers is shown in Figure 7A (Mulakala & Reilly, 2005). In this model, the CBM is inserted under a cellulose chain like a wedge to separate the chain from the cellulose network.…”
Section: Knowledge Gapmentioning
confidence: 99%